STUDI APLIKASI KERAMIK ZnBiCo SEBAGAI TERMISTOR NTC - Syarif, Dani Gustaman; Henny, Henny; Suhandi, Andi (MESIN, 2006)
STUDY ON THE APPLICA TION OF ZnBiCo CERAMICS AS NTC THERMISTORS. A study onthe application ofZnO-Bi203-CoO (ZnBiCo) ceramicsfor NTC thermistors had been carried out. The aim ofthisstudywas tofind alternative NTCthermistors. The studywas done as follow. Powder ofZnO, CoO andBi203 with concentration of Bi203 of 0, 0.25, 0.5, and 0.75 mole % and of CoO of 2 mole % werehomogeneously mixed. The mixedpowder was pressed with pressure of3.9ton/cm2 into pellets and sinteredat HOCfC in airfor 1 hour. The sintered pellets were evaluated using x-ray diffraction (XRD), opticalmicroscope andSEM(Scanningelectron microscope). Resistivity-temperature characteristic (p-Tcurve) wasdetermined through measurement of resistivity at various temperatures from room temperature to WCfC.XRD andmicrostructure datashowed thatmostofCoOformed a solid solution withZnOmatrix while Bi203was segregated at grain boundaries as ZnO,24Bi203 second phase. It was known that the all ceramicsproducedin this studyhad the same structure i.e. hexagonal. It was known also that the addition ofBi203increased the average grain size of the ZnBiCo ceramics. Electrical data showed that Bi203 increased theroom temperature resistivity (ps^) and the thermistor constant (B) of the ZnBiCo ceramic thermistors. Thethermistor constant and sensitivity (a) of the thermistor ceramics in this study were relatively high (largerthan 200(fKfor Band larger than 2.2 (Â°K)~lfor a)andsuitableforcommercial application.